Pemeliharaan Drainase di Desa Bukit Rata Sebagai Bentuk Pengabdian Kepada Masyarakat - Nanda Arfan Fitra; Ilhamdi Almi; Isra Wesi; Yuliana Fitri; Jasniwan Jasniwan; Mahmud Basuki (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Bukit Rata Village is a part of Kute Panang District, Central Aceh District, where high rainfall often occurs, so it is necessary to anticipate handling drainage problems. Based on the results of field observations, it was found that the main problems related to drainage were the accumulation of garbage and sedimentation which caused inhibition of drainage performance so that it was necessary to clean, handle and maintain the canals so that the drainage system could function optimally. Community service activities by carrying out mutual cooperation activities so as to increase the enthusiasm of residents in protecting the environment by taking care of drainage properly and correctly. The method used is to go directly to the field to clean the drainage channels which are covered with grass and various sediments, discussions, and direct practice in the field. The implementation of efforts to increase efficiency, care and maintenance of drainage consists of several stages, namely (1) observation stage, (2) program planning, (3) outreach, and (4) directing the implementation of the drainage maintenance program. As a result of this activity, the community is enthusiastic about participating in mutual cooperation activities to clean the drainage so that the drainage is clean and returns optimally according to its function.